The Concept of Libraries in Islamic Education: An Analysis of Ahmad Tsalby's Thought in the Book At-Tarbiyah al-Islamiyah - Saputra, Sukma Eka; Basuki, Basuki (Inkunabula: Journal of Library Science and Islamic Information, 2026)
This study aims to analyze Ahmad Tsalby's thought in At-Tarbiyah al-Islamiyah regarding the concept of libraries in Islamic education, which are positioned as an integral part of the educational process. This research employs a library research method, with the primary data source being At-Tarbiyah al-Islamiyah written by Ahmad Tsalby, while secondary data sources are obtained from books and relevant scholarly journal articles. The data were analyzed using content analysis techniques to identify Ahmad Tsalby's conceptual ideas concerning the functions of libraries within the framework of Islamic education. The findings reveal that, according to Ahmad Tsalby, Islamic libraries have four main functions: as a means for the development of knowledge, as guardians of the Islamic intellectual tradition, as centers of dynamic scholarly activity, and as a foundation for the formation of ethics and morals toward knowledge. These findings indicate that libraries function not merely as places for storing collections, but also as educational institutions that support the achievement of Islamic educational goals through the development of scholarly traditions and the internalization of Islamic values. Therefore, the concept of libraries proposed by Ahmad Tsalby remains relevant to be contextualized in the management of libraries within contemporary Islamic educational institutions.AbstrakPenelitian ini bertujuan untuk menganalisis pemikiran Ahmad Tsalby dalam kitab At-Tarbiyah al-Islamiyah mengenai konsep perpustakaan dalam pendidikan Islam yang diposisikan sebagai bagian integral dari proses pendidikan. Penelitian ini menggunakan metode penelitian kepustakaan dengan sumber data primer berupa kitab At-Tarbiyah al-Islamiyah karya Ahmad Tsalby, sedangkan sumber data sekunder diperoleh dari buku dan artikel jurnal ilmiah yang relevan. Data dianalisis menggunakan teknik analisis konten untuk mengidentifikasi gagasan konseptual Ahmad Tsalby mengenai fungsi perpustakaan dalam kerangka pendidikan Islam. Hasil penelitian menunjukkan bahwa menurut Ahmad Tsalby perpustakaan Islam memiliki empat fungsi utama, yaitu sebagai sarana pengembangan ilmu pengetahuan, penjaga tradisi intelektual Islam, pusat aktivitas keilmuan yang hidup, serta landasan pembentukan etika dan akhlak terhadap ilmu. Temuan ini menunjukkan bahwa perpustakaan tidak hanya berfungsi sebagai tempat penyimpanan koleksi, tetapi juga sebagai institusi edukatif yang mendukung tercapainya tujuan pendidikan Islam melalui pengembangan tradisi keilmuan dan internalisasi nilai-nilai Islam. Oleh karena itu, konsep perpustakaan yang dikemukakan Ahmad Tsalby memiliki relevansi untuk dikontekstualisasikan dalam pengelolaan perpustakaan pada lembaga pendidikan Islam kontemporer.